2012
DOI: 10.1097/brs.0b013e318247821b
|View full text |Cite
|
Sign up to set email alerts
|

SF-6D Values Stratified by Specific Diagnostic Indication

Abstract: Patients with lumbar degenerative disorders have health state values similar to patients with chronic renal disease, Crohn's disease, or coronary artery disease. Health state values of patients with different indications for surgery differ at baseline and after surgery. Revision cases have worse baseline SF-6D scores and less improvement in scores at 2 years after surgery than primary cases. Further studies are needed to gain a greater understanding of health state utility values in patients with lumbar degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Therefore, the importance of these aspects should be weighted in the clinical setting when considering surgical indications based on HRQOL. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the importance of these aspects should be weighted in the clinical setting when considering surgical indications based on HRQOL. 21 …”
Section: Discussionmentioning
confidence: 99%
“…As for the short form-36 (SF-36) and oswestry disability index (ODI), clinicians have been introduced to the concept of the minimal clinically important difference 21 22 23 and substantial clinical benefit. 24 Likewise, the EQ-5D to determine health state values in patients with DLSD may be more appropriate than the SF-6D.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Bess et al, 1 Bridwell et al, 4 and Glassman et al 10 report average baseline Oswestry Disability Index scores for surgical spine deformity patients of 33, 37, and 34, respectively, much lower (lesser disability) than the average Oswestry Disability Index score of 56 reported in Glassman et al 9 in their 2012 study of single-level posterolateral lumbar fusion. Carreon et al 5 also reported an average baseline SF-6D of 0.53 among patients with scoliosis, which was the highest average baseline score among all diagnostic categories considered.…”
Section: Discussionmentioning
confidence: 88%
“…For example, within the diagnosis of DDD, admittedly a poor indication for fusion, Glassman et al have established a subset of patients who experienced excellent outcomes after lumbar fusion. 2,13 Unfortunately, the ICD-9-CM diagnostic categories are not capable of distinguishing this subset from the category as a whole.…”
Section: Discussionmentioning
confidence: 99%